Exploring User Awareness and Accessibility of N-LIST e-Resources: A Case Study - Gautam, Mahima; Gulati, Anjali (Journal of Information and Knowledge, 2025)
Library consortia support collaborative sharing of resources among participating libraries, which can be formal or informal agreements. This cooperation enables libraries to expand their resource offerings and improve services. Numerous consortia exist, including INFLIBNET’s N-LIST program, which provides affordable and valuable access to resources for college students (Waghmode, 2014). This study explores the awareness and accessibility of electronic resources offered through the N-LIST program among faculty members and students of selected Colleges affiliated with the University of Lucknow. A structured questionnaire was administered to 250 respondents, and 210 completed responses were analysed to examine the extent of awareness and accessibility of N-LIST’s e-resources. The findings indicate that a significant number of faculty members and students access N-LIST e-resources every week, suggesting a need for these resources. The study also revealed the satisfaction level of Faculty and Students with regard to N-LIST e-resources. 54% of respondents agreed that a ‘user education orientation program’ was provided by college libraries. Based on these findings, it is recommended that college libraries must organise periodic training programs to promote awareness and help develop optimal skills among users for proper utilisation of e-resources, particularly those offered through the N-LIST consortium.